Modeling of waste outputs in the aquatic environment from a commercial cage farm under neotropical climate conditions - Bueno, Guilherme Wolff [UNESP]; Bernal, Francisco E. M.; Roubach, Rodrigo; Skipper-Horton, James Owen; Sampaio, Fernanda Garcia; Fialho, Naor S. [UNESP]; Bureau, Dominique P. (Inter-research, 2023)
The present study used a bioenergetics modeling approach to estimate the solid and dissolved waste outputs of a Nile tilapia Oreochromis niloticus net-cage farm. Historical production data for 30 cages were obtained from a commercial farm in the Chavantes Reservoir, Sao Paulo State, Brazil. In addition, an experiment was carried out in 4 net-cages at the farm to validate this dataset and collect fish samples. A total of 32400 tilapias with an initial weight averaging 35 +/- 2.73 g were equally distributed in the experimental net cages. After 210 d, the fish showed a final individual weight of similar to 789 +/- 5.12 g. Fish growth performance was monitored, and body composition was analyzed each month. Digestibility trials of commercial diets used for juvenile stages JVI and JVII and market weight were performed. Relationships of body weight with body content data of water, protein, fat, ash, gross energy, phosphorus, and nitrogen were evaluated by regression analysis. The total digestible energy requirement and estimated residues of the fish were assessed using the factorial bioenergetics model, adapted to the growing conditions of a neotropical reservoir. The model estimated similar to 320 kg of total solid waste released per tonne of tilapia, including similar to 10 kg of solid nitrogen and similar to 5 kg of solid phosphorus. Approximately 3 and 47 kg of dissolved phosphorus and nitrogen, respectively, were estimated per tonne of tilapia. The bioenergetics model is a valuable and equitable method for assessing and monitoring waste outputs. It can improve the nutritional and environmental efficiency of aquaculture activities, helping producers to reduce feed costs while strengthening the environmental sustainability of aquaculture.
Keywords: Aquaculture; Bioenergetics; Carrying capacity; Circular economy; Fish farm waste; Tilapia